Transición de radio análoga a radio digital: Caso Radio Libre - Burgos Duque, Nella Estefania (2022)
The present case study was born as a result of an exploratory study on a very poorly covered problem that turns out to be very common among the main radio media in Ecuador. The transition from analog radio to digital radio. Objective: To analyze the process of transition from analog radio to digital radio, special case Radio Libre, of the Babahoyo Canton, Los Ríos Province. Methodology: A qualitative approach was obtained according to the characteristics of the study context; developing an exploratory type research and with a non-experimental design. The researcher selected an intentional sample of two announcers and a manager who owns Radio Libre 93.9 Fm, from Babahoyo Canton, Los Ríos Province. Instrument: A structured questionnaire of questions as an interview was proposed and applied to learn about the transition process in Radio Libre 93.9 Fm, of the Babahoyo Canton, Los Ríos Province. Results: The process of transition from analog radio to digital radio has had important changes in terms of the positioning of the radio station compared to its predominant premises. The transition process has benefited not only contemporary listeners but listeners as well; thus, highlighting the need to continue carrying out analog broadcasting despite the arrival of new platforms and digital media. There is a specific organization and control over the programs, segments and the level of professionals for broadcasting them. Conclusions: Radio Libre 93.9 Fm, from the Babahoyo Canton, Los Ríos Province, has become one of the main provincial radio stations with the best tuning and positioning to date, based on listener loyalty.